Entrepreneurial Intentions Among High School Students in Samarinda City : Influence of Learning Culture, Need for Achievement, and Family Environment Through Self-Efficacy - Fitria, Umi; Kartini, Enny; Surahman, Surahman (LPPM Universitas Pendidikan Mandalika, 2025)
This study aims to analyze the effect of learning culture, achievement needs, family environment and self-efficacy on students' entrepreneurial interest. This research was conducted in high schools in Samarinda City. In this study, the method used was quantitative with a survey approach. The population in this study was 1,562 grade XII students in Samarinda City.Â The sample was taken using a proportional random sampling technique which amounted to 410 respondents. The data collection techniques used were questionnaires, interviews, and documentation. Data analysis used Confirmatory Factor Analysis (CFA). Data were analyzed using descriptive and inferential statistical techniques. The model fit test uses Structural Equation Modeling (SEM) with the LISREL program. Before conducting SEM analysis, validity and reliability tests were conducted to ensure that the measurement instruments used were of good quality. A normality test was also conducted to ensure that the data obtained met the assumptions required for SEM analysis. The results of this study are: (1) Need for achievement and family environment have a positive and significant effect on entrepreneurial interest, while the learning culture and self-efficacy do not affect entrepreneurial interest. (2) Learning culture, need for achievement and family environment affect self-efficacy. (3) Learning culture, need for achievement and family environment do not affect entrepreneurial interest through self-efficacy. Therefore, it important for schools and parents need to create an environment that supports and encourages students to pursue entrepreneurship. Schools can develop a curriculum that is more integrated with entrepreneurial practices, while parents can provide the necessary support to help their children pursue their dreams.